Topical minocycline foam 4%: Results of four phase 1 studies evaluating the potential for phototoxicity, photoallergy, sensitization, and cumulative irritation. (1st January 2019) - Dosik, Jonathan; Ellman, Herman; Stuart, Iain
Abstract: FMX101 4% contains 4% micronized minocycline (as an HCl) formulated in a lipophilic foam vehicle for topical administration. FMX101 4% has been shown to be an effective and well-tolerated treatment for moderate-to-severe acne in three Phase 3 pivotal studies, however, skin sensitization and toxicity potential remains to be fully evaluated. Four single-center, randomized, controlled, within-subject comparison studies were conducted to evaluate the potential for phototoxicity, photoallergy, skin sensitization, and cumulative skin irritation with topical administration of FMX101 4% and the corresponding vehicle. Across the four studies, healthy male and non-pregnant female volunteers (age ≥18 years) were randomized to FMX101 4%, vehicle, or other controls. In the phototoxicity study, treated skin was irradiated at 3 and 24 hr post-application, and local tolerability was assessed pre- and post-irradiation. In the photoallergy study, the skin was treated and irradiated (post-24 hr) twice weekly for 3 wk (induction phase), rested for 10–17 d, and naive skin sites were treated and irradiated (challenge phase); skin reactions were assessed after patch removal and post-irradiation. In the sensitization study, the skin was treated for 3 wk (induction phase), then rested for 10–14 d, and naive skin sites were treated for 48 hr (challenge phase); contact sensitization was assessed for both phases. In the cumulative irritation study, treatment and vehicle were applied daily for 21 d; skin irritation was assessed after each application. In all studies, standard safety assessments were conducted. A total of 32, 56, 233, and 42 subjects were enrolled in the phototoxicity, photoallergy, sensitization, and skin irritation studies, respectively. There was no evidence of phototoxicity, photoallergy, skin sensitization, or skin irritation potential with FMX101 4%. Few adverse events, mostly mild to moderate, were reported. In conclusion, FMX101 4% appeared to be well tolerated and non-irritating, and was considered to be non-sensitizing, non-phototoxic, and non-photoallergic.